Pembuatan Barcode Buku Perpustakaan di SD Negeri 112 Pekanbaru - Dora Amelya; Winda Amelia; Afrina Oktoberia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This community service activity aims to improve the library management system at SD Negeri 112 Pekanbaru through the implementation of barcode technology. The main problem faced by schools is the manual system of recording and searching for books, which causes difficulties in data collection and maintenance of book collections in the library. The method of activity implementation includes the stages of making, training, and implementing the library barcode system. The activity was carried out for one month by involving library staff and several LP3I PSDKU Pekanbaru Polytechnic lecturers who helped make barcodes and attach them to books in the library. The service process begins with a needs analysis, followed by training in making barcodes, using the barcode system, and installing a supporting device system using a cellphone to read barcodes. The results of the activity showed a significant increase in the efficiency of library book management. The implemented barcode system facilitates the process of borrowing, returning, and inventorying books. The conclusion of this service activity is the successful implementation of the barcode system in the library, which makes a positive contribution in improving the quality of school library services. The next recommendation is the development of a more comprehensive and sustainable digital system.